Analisis pengaruh investasi swasta, Belanja modal, dan upah minimum kota (UMK) terhadap penyerapan tenaga kerja di Kota Bandar Lampung dalam perspektif Ekonomi Islam - Salsabila, Hana Zalfa; Susanto, Is; Rahman, Taufiqur (Journal of Information System, Applied, Management, Accounting and Research, 2025)
Labor absorption is one of the main challenges in regional economic development. To achieve optimal labor absorption, this can be done through increased investment from the private sector and government in the form of capital expenditure and city minimum wage. This study aims to analyze the effect of private investment, capital expenditure, and city minimum wage (UMK) on employment in Bandar Lampung City in the perspective of Islamic economics. This type of research is quantitative research with multiple linear regression analysis methods using SPSS 25 software. The data used in this study are secondary data in the form of time series data within 11 years starting from 2013 to 2023. The results of this study partially show that only the capital expenditure variable has an insignificant negative effect on labor absorption while private investment and city minimum wage have a significant positive effect on labor absorption. Then together show that private investment, capital expenditure and city minimum wage together have a positive and significant effect on employment in the city of Bandar Lampung. In the perspective of Islamic economics regarding private investment, capital expenditure and city minimum wage on labor absorption in Bandar Lampung city is in accordance with the principles of Islamic economics because it is based on the welfare of the community.